(untitled) (Fiep Bulletin - online, 2015)
The survey aimed to ascertain how neuromuscular and flexibility values in bus drivers aged 25-57 years varied over a time interval of two years. The precarious occupational health, for the bus drivers, is relatively frequent among these workers. Several national and international studies have shown that the bus drivers fall ill in and die a different way compared to the population in general. The study was observational, scored for two consecutive years and consisted of observation sat three different times, the values of the endurance test of the abdomen, upper limb strength and flexibility (sit-and-reach). The study sample consisted of 179 males, aged 25-57 years, all bus drivers belonging to a company of interstate transportation from Bahia-Brazil. The subjects were divided in to five age groups. The data collected were introduced into referred computerized program SPSS11.0, to apply statistical treatments. This study highlights that acrros physical assements undertaken individuals present in general, an improvement in their neuromuscular indicators over time. We still need to deepen into more scientific studies about major changes in working conditions and workplace, and healthy habits of the bus drivers that are required in order to minimize the impact on the occupational health of these workers. We emphasize the need to implement programs for health promotion and better working conditions for these workers.